LEGAL REGULATIONS OF MEDICAL TOURISM IN UKRAINE - Yamnenko, Tetiana; Zmievska, Angelina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Objective: to analyze the current state of development of medical tourism in terms of benefits and challenges. Research methods: logical, formal-dogmatic, comparative-legal, etc. Results: definition of the term «medical tourism», study of the mechanism of legal regulation of medical tourism. Discussion: possibilities of application of various doctrinal approaches to the explanation of the concepts of medical tourism, medical and health tourism, introduction of tourist activity and application of the legal mechanism to these concepts. Medical tourism is one of the important elements in the field of tourism, which comprehensively contributes to the development of health care and health care, contributes to filling the state budget through foreign visitors and attracting foreign investment, as well as positively affects the overall image of the state. in the world. Given the realities of today, it can be said that there are no harmonized international standards for the assessment, quality and safety of tourism professionals, other than ethical. Therefore, it is difficult to talk about all the consequences of the development of medical tourism, including negative ones. Therefore, court cases on trade in health care services need documentation. More information and scientific understanding is needed before considering any regulation. Thus, today there is an urgent need to develop and adopt the Law of Ukraine «On Medical Tourism», which should interpret and consolidate the theoretical basis, which is currently not disclosed at all, to consolidate the rights, responsibilities and interests of medical tourism, to resolve issues with their legal protection, which is also a problem now. And, of course, medical tourism should have more government support and funding, as is the case in most developed countries.